Individualism/collectivism and charitable donations: An empirical analysis at the national, regional, and personal levels - Yan Cui; Zhi-Qiang Jiang; Li Wang; Wei-Xing Zhou (Journal of Management Science and Engineering)
Online donation platforms are instrumental in facilitating individual charitable giving by leveraging the confluence of financial technology and mobile social networks. Despite the impact of these technological advancements, the role of culture in shaping the motivations and behaviors of donors remains an open area for exploration. By analyzing three different datasets, we elucidate the relationship between individualism/collectivism and charitable donations at the national, regional, and personal levels. A remarkable U-shaped pattern is revealed between individualism/collectivism and charitable donations. It is also found that the personal reputation strengthens the positive effect of individualism/collectivism on the donation amount, with a notably stronger influence on individualists than on collectivists. Furthermore, collectivists prefer to allocate donations to acquaintances, whereas individualists tend to direct their contributions towards strangers. Our results not only provide an understanding of the psychological and social mechanisms that underlie cultural influences on charitable giving but also highlight the importance of considering cultural contexts when designing strategies to encourage and enhance charitable donations.